2016
DOI: 10.16965/ijims.2016.146
|View full text |Cite
|
Sign up to set email alerts
|

A Study to Assess the Effectiveness of Self-Instructional Module on Home Management of Diarrhea among Mothers of Under Five Children in Selected Hospital at Bangalore

Abstract: BACKGROUND

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 5 publications
2
2
0
Order By: Relevance
“…Furthermore, the current study found that the number of the mothers living in nuclear 91(45.5) and mothers living in extended family accounted 109(54.5). These result agree with the study in (Bangalore) who that the majority number of the mothers (70%) belongs to joint family and 30% belong to nuclear family [1] .…”
Section: Discussion Of Socio-demographic Characteristics For Mothers (In the Table 1)supporting
confidence: 92%
See 3 more Smart Citations
“…Furthermore, the current study found that the number of the mothers living in nuclear 91(45.5) and mothers living in extended family accounted 109(54.5). These result agree with the study in (Bangalore) who that the majority number of the mothers (70%) belongs to joint family and 30% belong to nuclear family [1] .…”
Section: Discussion Of Socio-demographic Characteristics For Mothers (In the Table 1)supporting
confidence: 92%
“…Findings reveal that the majority highest percentage of the age mothers is located in age group of (25-30) in the table (1). This finding similar to a study done by (Artifasari & Irawati, 2020).…”
Section: Discussion Of Socio-demographic Characteristics For Mothers (In the Table 1)supporting
confidence: 86%
See 2 more Smart Citations